Synthesis, electrochemistry, spectroelectrochemistry and electrocolorimetry of phthalocyanine-anthraquinone hybrids - KOCA, ATIF (ELSEVIER SCIENCE SA, 2010)
The tetra substituted metallophthalocyanines 2 and 3, soluble in common organic solvents, bearing four 2-(9,10-dioxo-9,10-dihydro-anthracen-2-yl-methyl)-malonic acid diethyl ester functionalities were synthesized from the corresponding phthalodinitrile 1 and divalent metal salts at 170 C in fused state. Reaction of with manganese (2+) acetate in n-pentanol led to the manganese (3+) phthalocyanine 4. Furthermore, the unsymmetrical copper phthalocyanine 5 containing one 2-(9,10-dioxo-9,10-dihydroanthracen-2-yl-methyl)-malonic acid diethyl ester moiety was synthesized using a statistical approach. The new compounds were characterized by elemental analysis together with FT-IR, H-1-NMR, C-13-NMR, and UV-vis spectroscopy and via mass spectrometric analysis. The electrochemical, in situ spectroelectrochemical, and in situ electrocolorimetric measurements represent that while MPcs give common ring-based and/or metal-based electron transfer processes, these processes were considerably affected with the redox processes of the AQ units attached to the phthalocyanine ring. At the same time attachments of the AQ units to the phthalocyanine rings improve the reversibility of the AQ units due to the electron donor-acceptor interaction between the AQ units and phthalocyanine ring. The AQ units also alter the color states of the phthalocyanines. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine-anthraquinone hybrids; Electrochemistry; Unsymmetrical phthalocyanines; Spectroelectrochemistry; IN-SITU; SUBSTITUTED COBALT; COMPLEXES; DERIVATIVES; PORPHYRIN; REDUCTION; MANGANESE; 9,10-ANTHRAQUINONE; SPECTROSCOPY; POSITIONS